Viral hepatitis A in children: a false prosperity? - L. G. Goryacheva; A. U. Mirzova; A. L. Mukomolova (Детские инфекции (Москва))
The article presents current data on the state of the issue of Hepatitis A (HA) in children in the Russian Federation and describes clinical and epidemiologic features of rare cases of severe course of the disease, as well as pathogenetic mechanisms of liver damage mediated by cell immune response. Objective. To identify clinical and epidemiologic features of the modern course of HA and its outcomes in children of Saint Petersburg within the period of 2018— 2023. Materials and methods. The study included 89 children diagnosed with HA, undergoing treatment at the Children's Research and Clinical Center for Infectious Diseases from 2018 to 2023. The analysis of disease progression in this group of patients was presented using clinical-anamnestic, epidemiologic, biochemical, virologic and instrumental data. Results. The analysis of infection sources showed a high frequency of HA infection within the family (44.9 ± 0.8%) and significantly less in childcare facilities and schools (7.9 ± 1.0%). The frequency of children with unidentified sources of infection remained high (47.2 ± 0.7%). One-third of all disease cases were imported from southern regions. Most hospitalized children had icteric HA (64.0 ± 0.6%) of moderate severity (79.8 ± 0.5%). Severe HA was observed in 6 patients (6.7 ± 1.0%). During the study, 17 patients (19.1 ± 0.9%) had a prolonged, complicated course of the disease, including ascites and aplastic anemia (12.6 ± 2.2%). Ascites was found in 4 patients with severe severity and in 5 patients with moderate severity of HA. Conclusions. Currently, there is an upward trend in the incidence of HA in the Russian Federation and Saint Petersburg, especially among schoolchildren (56.2%). A rather high frequency of severe (6.7%) and complicated forms (19.1%) of the disease is observed, and the growth of ascites and aplastic anemia cases in HA draws particular attention.